The Modern Interpretation of the Prophet's Sunnah (Purposes and Risks) - Alfathi, Hamzah Faiei Ibraheem (Journal of Islamic Sciences, 2023)
The main objective of this research is to explain the meaning of modern interpretation of the Prophet's Sunnah, explore its purposes, and show its implications.The methodology used in this study is the analytical-critical approach that is based on analyzing the views of the contemporaries in explaining, understanding and applying the Sunnah of the Prophet to real life issues.Main Research Themes1- Explaining the concept of modern interpretation of the Prophet’s Sunnah, and disclosing the purposes of those who advocate it.2- Unfolding the approach of modern interpreters when interpreting and analyzing religious texts.3- Showing several examples that illustrate how corrupted modern interpretation is, and explore its danger implications for the fundamentals of religion.The research concluded with the most important results:1- Undermining the concept of modern interpretation of religious fundamentals.2- Modern interpretation is a westernized idea to demolish the facts of religion.3- Modern interpreters depend on deviant approaches and the views of deviant sects.
Keywords: Interpretation; modern; Sunnah